UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MELALUI SUPERVISI AKADEMIK YANG BERKELANJUTAN DI SMK NEGERI 4 PADANGSIDIMPUAN - Budiman Sihombing (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2018)
This research was to look at the percentage of academic supervision the school principal can raise the competence of teachers in the preparation of the syllabus and the RPP. The location of the research is on the CMS State 4 Padangsidimpuan in Jln. Desa Plantations Pijorkoling plantations of Kec. Padangsidimpuan Southeast Of The City Padangsidimpuan. Implementation time is planned for one month starting August 1 to October 30, 2015. This research was carried out on its own writers, and writers assisted by curriculum Developers Team SMK Negeri 4 Padangsidimpuan consisting of the principal, Curriculum, and Waka Waka Studentship. This research was conducted with the research methods class action that lasted for 2 cycles. Each cycle consists of the stages of planning, implementation, observation and reflection. The results obtained, namely the increasing number of good teachers syllabus of 31% to 83% after academic supervision. In addition the number of RPP a good quality also increased from 31% to 89%. Increased competency of teacher in drawing up the syllabus and the RPP is good increased by 52% and 58%. The implementation of individual supervision is suitable to improve the competence of teachers in drawing up the syllabus and RPP during this Administration still remains a difficult requested from our teachers. To test it, we can use the class supervision. For the other trustees are expected to give a clearer input and directional in formation against the teacher.